Age-associated changes in muscle activity during isometric contraction - Arjunan, Sridhar P.; Kumar, Dinesh K. (Muscle & nerve, 2013)
Introduction: We investigated the effect of age on the complexity of muscle activity and the variance in the force of isometric contraction. Methods: Surface electromyography (sEMG) from biceps brachii muscle and force of contraction were recorded from 96 subjects (20–70 years of age) during isometric contractions. Results: There was a reduction in the complexity of sEMG associated with aging. The relationship of age and complexity was approximated using a bilinear fit, with the average knee point at 45 years. There was an age‐associated increase in the coefficient of variation (CoV) of the force of muscle contraction, and this increase was correlated with the decrease in complexity of sEMG (r2 = 0.76). Conclusions: There was an age‐associated increase in CoV and also a reduction in the complexity of sEMG. The correlation between these 2 factors can be explained based on the age‐associated increase in motor unit density. Muscle Nerve 47: 545–549, 2013